2002
DOI: 10.1046/j.1532-5415.2002.50202.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Mortality in Treating Acutely Sick, Frail Older Patients in a Geriatric Evaluation and Management Unit. A Prospective Randomized Trial

Abstract: Treatment of acutely sick, frail, older patients in a GEMU substantially reduced mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
168
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(181 citation statements)
references
References 28 publications
2
168
0
8
Order By: Relevance
“…One suggestion for meeting this goal was to change the way health professionals were educated; hence, an initiative on professional education for collaborative patient-centred practices was launched. Since then, other interprofessional initiatives have been launched within the provinces across Canada [10,21].A Health Canada review of interprofessional education [10] found some evidence that post-licensure professional collaborations can improve healthcare processes and outcomes in some areas of geriatric care [22,23], congestive heart failure management [24], and neonatal care [25], but no reliable evidence on the effectiveness of interprofessional education at the undergraduate or pre-licensure level could be found. One of the notions supporting interprofessional education at the undergraduate level is that it may assist students in appreciating various roles within healthcare, increase comfort in working with other health professionals, and hence increase post-licensure interprofessional practice.…”
mentioning
confidence: 99%
“…One suggestion for meeting this goal was to change the way health professionals were educated; hence, an initiative on professional education for collaborative patient-centred practices was launched. Since then, other interprofessional initiatives have been launched within the provinces across Canada [10,21].A Health Canada review of interprofessional education [10] found some evidence that post-licensure professional collaborations can improve healthcare processes and outcomes in some areas of geriatric care [22,23], congestive heart failure management [24], and neonatal care [25], but no reliable evidence on the effectiveness of interprofessional education at the undergraduate or pre-licensure level could be found. One of the notions supporting interprofessional education at the undergraduate level is that it may assist students in appreciating various roles within healthcare, increase comfort in working with other health professionals, and hence increase post-licensure interprofessional practice.…”
mentioning
confidence: 99%
“…23 In verschillende studies is gewezen op het belang van gespecialiseerde geriatrische afdelingen, vaak in combinatie met multidisciplinaire nazorg, zoals casemanagement na ontslag uit het ziekenhuis met revalidatiemogelijkheden. 19,[23][24][25][26] Ziekenhuisgerelateerd functieverlies bij oudere patiĂ«nten is een onderschat probleem. In Nederland zijn de medische behandeling en verpleegkundige zorg grotendeels gericht op de gediagnosticeerde ziekte, met weinig aandacht voor een reactiverende behandeling om functieverlies bij de oudere patiĂ«nt te voorkomen.…”
Section: Achtergrondunclassified
“…Er zijn voldoende aanwijzingen dat deze aanpak leidt tot een betere functionele status, betere kwaliteit van leven van de oudere patiĂ«nt gedurende 12 maanden na de ziekenhuisopname, minder valincidenten, kortere ziekenhuisopname, minder (her)opnamen in ziekenhuizen en verpleeghuizen, beter geestelijk welzijn van de mantelzorgers, en lagere sterfte. 13,15,18,[20][21][22][23]25,[27][28][29][30] Beschrijvingen …”
Section: Achtergrondunclassified
See 1 more Smart Citation
“…Geriatric giants (Chase et al. , 2000;Sherman, 2003;) syndrom of terminal geriatric deterioration -FTT ("failure to thrive") The above mentioned geriatric syndromes not always threaten patient's life but they essentially influence quality of their following life (Fauci et al, 2008;Salvedt et al., 2002). Patients become fully dependent on other people´s assistance (family, friends, neighbours, community services).…”
Section: Geriatic Syndromes and Frailty As Golden Grale Of Geriatric mentioning
confidence: 99%